Teacher's Professional Competence on Student Learning Outcomes - Rahmad Kasim; Usman Moonti; Sudirman Sudirman (Journal of Economic and Business Education, 2023)
The purpose of this study was to determine "The Influence of Teacher Professional Competence on Learning Outcomes of Class X Social Studies Students in Economics Subjects at SMA Negeri 1 Kabila.This study uses a quantitative approach with the method used is the method of Simple Linear Regression Analysis with a sample of 24 students. Data collection techniques used in this study were interviews, questionnaires, and data analysis techniques in this study using simple regression.The results showed that there was an influence of teacher professional competence on the learning outcomes of class X social studies students in economics subjects at SMA Negeri 1 Kabila. The influence of teacher professional competence on student learning outcomes reaches 37.1% while the remaining 62.9% is influenced by other variables not examined.